A system for coarse-grained location-based synchronisation - Coelho, André (2010)
This paper describes a system for supporting coarse-grained location-based synchronisation. This type of synchronisation may occur when people need only some awareness about the location of others within the specific context of an on-going activity. We have identified a number of reference scenarios for this type of synchronisation and we have implemented and deployed a prototype to evaluate the type of support provided. The results of the evaluation suggest a good acceptance of the overall concept, indicating that this might be a valuable approach for many of the indicated scenarios, possibly replacing or complementing existing synchronisation practices.